2013
DOI: 10.1177/1746197913475768
|View full text |Cite
|
Sign up to set email alerts
|

Teaching human rights? ‘All hell will break loose!’

Abstract: Human rights education is a prominent concern of a number of international organisations and has been dominant on the United Nations' agenda for the past 20 years. The UN Decade for Human Rights Education (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004) has been followed by the World Programme for Human Rights Education (2005-ongoing) and the recently adopted UN Declaration on Human Rights Education and Training. This article shares findings from a project that aimed to gauge the knowledge of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 19 publications
3
31
0
2
Order By: Relevance
“…There is a common belief among many adults, but especially teachers, practitioners and families, that children have too many rights and not enough responsibilities (Cassidy et al, 2014). In fact, Waldron and Oberman (2016) found that teachers recognize the importance of HRE but are more focused on promoting a culture of conformity and responsibility.…”
Section: Excessive Attention Focused On the Teaching Of Responsibilitiesmentioning
confidence: 99%
“…There is a common belief among many adults, but especially teachers, practitioners and families, that children have too many rights and not enough responsibilities (Cassidy et al, 2014). In fact, Waldron and Oberman (2016) found that teachers recognize the importance of HRE but are more focused on promoting a culture of conformity and responsibility.…”
Section: Excessive Attention Focused On the Teaching Of Responsibilitiesmentioning
confidence: 99%
“…Strong support in national curricula is pointed out as necessary if rights education is to take place. Several studies have demonstrated that human rights often is a cross-curricular issue (Cayir and Türkan Bagli 2011;Cassidy, Brunner, and Webster 2013;Phillips 2016;Robinson 2017). That the responsibility for education about human rights is thereby spread over several school subjects can be both a strength and a risk.…”
Section: Research Into Rights Education In Formal Schoolingmentioning
confidence: 99%
“…Research that highlights the significance of the teacher for rights education has identified some obstacles for a successful rights education. One is that teachers' knowledge of human rights often seems to be insufficient (Cassidy, Brunner, and Webster 2013). Teachers themselves express uncertainty about human rights teaching, largely because they see human rights as a complex and multi-layered issue and are unsure about what to include and focus on, and how to teach human rights (Cayir and Türkan Bagli 2011).…”
Section: Research Into Rights Education In Formal Schoolingmentioning
confidence: 99%
“…As a consequence of this simplified model teachers tend to be seen as either compliant or as obstacles, and problems largely arise from teachers' ignorance of children's rights (Cassidy et al, 2014). For example, Howe and Covell (2005) have argued that teachers' often adopt a negative approach to CRE and Figue (2013) and Leung et al (2011) report that many teachers see children's rights as a threat to adult authority (thus failing to understand the appropriate role of adult duty bearers).…”
Section: Teachers As Implementersmentioning
confidence: 99%